1999
DOI: 10.1016/s0167-4889(99)00114-7
|View full text |Cite
|
Sign up to set email alerts
|

Apelin, the natural ligand of the orphan receptor APJ, is abundantly secreted in the colostrum

Abstract: By using a strategy that we have developed to search for the ligands of orphan seven-transmembrane-domain receptors [S. Hinuma et al., Nature 393 (1998) 272-276], we have recently identified a natural ligand, apelin, for the orphan 7TMR, APJ [K. Tatemoto et al., Biochem. Biophys. Res. Commun. 251 (1998) 471-476]. In this paper, we isolated rat and mouse apelin cDNAs, and analyzed the tissue distribution of apelin mRNA in rats. Although apelin mRNA was widely detected in a variety of tissues, the highest expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
327
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(348 citation statements)
references
References 25 publications
14
327
0
7
Order By: Relevance
“…Apelin-36 was the first of these shorter C-terminal sequences being described to bind and activate APJ [45]. Also Apelin-17, Apelin-13 and its pyroglutamyl isoform which is resistant to degradation, (Pyr1)-Apelin-13, were proven to act as functional ligands of APJ and in some cases exhibited much higher biological activity than Apelin-36 [45,17,18,25,46].…”
Section: Introductionmentioning
confidence: 99%
“…Apelin-36 was the first of these shorter C-terminal sequences being described to bind and activate APJ [45]. Also Apelin-17, Apelin-13 and its pyroglutamyl isoform which is resistant to degradation, (Pyr1)-Apelin-13, were proven to act as functional ligands of APJ and in some cases exhibited much higher biological activity than Apelin-36 [45,17,18,25,46].…”
Section: Introductionmentioning
confidence: 99%
“…It was subsequently demonstrated to be ubiquitously expressed with high expression levels in the lung, heart, medial layer of vessels and endothelial cells (3,4). The receptor is a G-protein coupled receptor signaling inhibition of adenylyl cyclase activity eliciting reduced cAMP formation (1,5) although also raise of intracellular calcium and activation of extracellularly regulated kinases (ERK) have been reported (6,7). The endogenous ligand for the apj receptor is apelin, which was initially demonstrated in stomach extracts in 1998 (8).…”
Section: Introductionmentioning
confidence: 99%
“…The endogenous ligand for the apj receptor is apelin, which was initially demonstrated in stomach extracts in 1998 (8). Later studies have shown that apelin mRNA is expressed in several tissues, as for example in several regions in the CNS, in the heart, lung, placenta, mammary gland and gastrointestinal tract (3,5,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ces données peuvent expliquer la présence de deux transcrits de taille différente, de 3,0 et 3,5 kb, en proportions variables suivant les tissus étudiés [7]. La proapéline a été isolée dans différentes espèces [5][6][7] et l'alignement des séquences de souris, rat, boeuf et homme a révélé une conservation stricte des 17 derniers acides aminés carboxyterminaux correspondant à l'apéline-17 ou K17F (Figure 1). In vivo, la proapéline donne naissance à différentes formes molé-culaires d'apéline : dans le cerveau et le plasma de rat, on retrouve majoritairement la forme pyroglutamyl de l'apéline 13, pE13F (Figure 1) et en plus faible quantité, K17F [8] ; dans le testicule et l'utérus, c'est l'apéline 36 qui prédomine, alors que, dans la glande mammaire, on retrouve à la fois l'apéline 36 et pE13F [9].…”
Section: L'apéline Un Inhibiteur Naturel De L'effet Antidiurétique Dunclassified